Migrant workers' occupation and healthcare-seeking preferences for TB-suspicious symptoms and other health problems: a survey among immigrant workers in Songkhla province, southern Thailand - Naing Tinzar; Geater Alan; Pungrassami Petchawan (BMC, 2012)
Abstract Background Much of the unskilled and semi-skilled workforce in Thailand comprises migrant workers from neighbouring countries. While, in principle, healthcare facilities in the host country are open to those migrants registered with the Ministry of Labour, their actual healthcare-seeking preferences and practices, as well as those of unregistered migrants, are not well documented. This study aimed to describe the patterns of healthcare-seeking behaviours of immigrant workers in Thailand, emphasizing healthcare practices for TB-suspicious symptoms, and to identify the role of occupation and other factors influencing these behaviours. Methods A survey was conducted among 614 immigrant factory workers (FW), rubber tappers (RT) and construction workers (CW), in which information was sought on socio-demography, history of illness and related healthcare-seeking behaviour. Mixed effects logistic regression modeling was employed in data analysis. Results Among all three occupations, self-medication was the most common way of dealing with illnesses, including the development of TB-suspicious symptoms, for which inappropriate drugs were used. Only for GI symptoms and obstetric problems did migrant workers commonly seek healthcare at modern healthcare facilities. For GI illness, FW preferred to attend the in-factory clinic and RT a private facility over government facilities owing to the quicker service and greater convenience. For RT, who were generally wealthier, the higher cost of private treatment was not a deterrent. CW preferentially chose a government healthcare facility for their GI problems. For obstetric problems, including delivery, government facilities were utilized by RT and CW, but most FW returned to their home country. After adjusting for confounding, having legal status in the country was associated with overall greater use of government facilities and being female and being married with use of both types of modern healthcare facility. One-year estimated period prevalence of TB-suspicious symptoms was around 6% among FW but around 27% and 30% in RT and CW respectively. However, CW were the least likely to visit a modern healthcare facility for these symptoms. Conclusions Self medication is the predominant mode of healthcare seeking among these migrant workers. When accessing a modern healthcare facility the choice is influenced by occupation and its attendant lifestyle and socioeconomic conditions. Utilization of modern facilities could be improved by reducing the current barriers by more complete registration coverage and better provision of healthcare information, in which local vendors of the same ethnicity could play a useful role. Active surveillance for TB among migrant workers, especially CW, may lead to better TB control.